722. Pharmacokinetics (PK) and Safety of Lefamulin (LEF) After Single Intravenous Dose Administration in Subjects With Impaired Hepatic Function - Wicha, Wolfgang; Marbury, Thomas C; Dowell, James A; Lykens, Lori; Leister, Cathie; Ermer, James; Gelone, Steven P (Open forum infectious diseases, 2019)
Background Patients with chronic liver disease (CLD) have impaired immune function, are prone to community-acquired bacterial pneumonia (CABP), and experience greater morbidity/mortality and healthcare costs than CABP patients without CLD. LEF, a novel pleuromutilin antibiotic (IV/oral) with primary liver elimination, was generally well tolerated and noninferior to moxifloxacin in two phase 3 studies of adults with CABP. We investigated the PK and safety of LEF and its main metabolite, BC-8041, in subjects with hepatic impairment. Methods In this open-label study, subjects were allocated to 1 of 3 groups based on hepatic function level; Moderate (Child-Pugh score 7–9) or Severe subjects (Child-Pugh score ≥10) were matched (gender, age, and weight) to subjects in the Normal group (normal hepatic function, no liver cirrhosis). Subjects received a single 1-hour 150 mg LEF infusion. Blood and urine samples were collected predose and over a 48-hour period postdose for PK analysis; plasma and urine were assayed for LEF and BC-8041 using validated assays. Safety assessments included treatment-emergent adverse events (TEAEs), labs, vital signs, and electrocardiograms. Results 27 subjects enrolled in and completed the study (n = 11, Normal; n = 8, Moderate; n = 8, Severe). Mean LEF and BC-8041 plasma concentration profiles were comparable across all hepatic function groups through the first 12 hours following the start of infusion. Subjects with hepatic impairment had slightly slower rates of elimination in the later elimination phases. LEF and BC-8041 exposures were similar across all hepatic function groups (table), and the majority of LEF and BC-8041 were excreted nonrenally. TEAEs were reported in 2 (18.2%) subjects in the Normal group, 2 (25%) in the Moderate group, and 1 (12.5%) in the Severe group. None of the TEAEs were serious or led to study drug discontinuation. No subject met Hy’s law criteria. Within 4 hours postdose, the maximum mean change from baseline in the QTcF interval was 12.4, 19.2, and 14.1 msec in the Normal, Moderate, and Severe groups, respectively. Conclusion No dosage adjustment for LEF appears to be required when treating subjects with hepatic impairment. LEF was generally well tolerated in all subjects regardless of hepatic functional status. Disclosures All authors: No reported disclosures